Restricting ionic liquid in a network comprising of GO/CNT as a separation membrane for efficient CO2 capture - Dinesh K. Behera; Fan Wang; Bratin Sengupta; Qiaobei Dong; Weiwei Xu; Shiguang Li; Miao Yu (Advanced Membranes)
The release of carbon dioxide (CO2) to the atmosphere remains a critical challenge in addressing climate change, with emissions from power plants being a primary contributor. Membrane-based separation processes offer cost-effective, robust, and energy efficient alternatives to CO2 capture from power plants. Ionic liquids (IL), known for their high CO2 affinity, low vapor pressure, and high thermal stability, are propitious materials for such separations. In this study, we try to address major challenges currently restricting IL-based membranes including the porous structure for loading IL and the loading procedure onto the porous structure. An ultrathin (∼230 ​nm) 2–dimensional composite network comprising of graphene oxide (GO) sheets intercalated carbon nanotubes (CNT) spatially confining IL targeting high CO2 permeance was designed and fabricated. An IL, 1-ethyl-3 methylimidazolium tetrafluoroborate ([EMIM][BF4] was used as the active separating medium. This GO/CNT hybrid network not only stabilizes the IL within the nanochannels because of interactions between cations of IL and negatively charged functional groups on GO (carboxyl, hydroxyl and carboxy groups) but also facilitates faster transport (increased nanochannels because of CNT incorporation) yielding a CO2 permeance of ∼600 GPU (one order of magnitude higher than reported membranes employing the same ionic liquid) and a CO2/N2 selectivity of 62 under humid conditions and elevated temperatures (up to 80 ​°C). Our approach provides a modified strategy of using ionic liquids in the solution form as opposed to most studies using pure form for obtaining a scalable, ultrathin, stable supported IL membrane.